Institutional translation and interpreting. Assessing practices and managing for quality, by Fernando Prieto Ramos (Ed.) - Tallone, Laura (2022)
Since Julianne House’sseminal paper (1977), proposals such as those of Sonia Colina (2008), Malcolm Williams (2009), Gloria Corpas Pastor (2006) or, more recently, Madeleine Schnierer (2020) are only a few examples of the growing scholarly attention devoted to translation quality assessment and control. As globalisation demands increasingly larger amounts of text to be handled in short periods of time, quality has in fact become a criticalissue, most especially in institutional settingsproducing documents of a sensitive nature, often with direct impact on peoples’ lives.